2016
DOI: 10.12927/hcq.2016.24482
|View full text |Cite
|
Sign up to set email alerts
|

The South West Local Health Integration Network Behavioural Supports Ontario Experience

Abstract: Creating a seamless system of care with improved system and patient outcomes is imperative to the estimated 35,000 older adults living with mental health problems and addictions in the South West Local Health Integration Network. Building on existing investments and those offered through the Behavioural Supports Ontario program, strategies to improve system coordination were put in place, crosssectoral partnerships were fostered, interdisciplinary teams from across the care continuum were linked, and education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Inter-and intra-cadre teamwork in delivery of complex, clientcentered care is of the essence to integrate care and strengthen linkages along a continuum of care that can span multiple clinical sites, and is essential to delivery of complex, client-centered care. 46 In NOC, rationalizing the distribution of case load has emerged as a potent method of integration that supports efficiency. Referral centers can get decongested when clients are cared for at the appropriate level of care, providing more opportunity for provision of better quality of care, including comprehensive care.…”
Section: Coordination Of Carementioning
confidence: 99%
“…Inter-and intra-cadre teamwork in delivery of complex, clientcentered care is of the essence to integrate care and strengthen linkages along a continuum of care that can span multiple clinical sites, and is essential to delivery of complex, client-centered care. 46 In NOC, rationalizing the distribution of case load has emerged as a potent method of integration that supports efficiency. Referral centers can get decongested when clients are cared for at the appropriate level of care, providing more opportunity for provision of better quality of care, including comprehensive care.…”
Section: Coordination Of Carementioning
confidence: 99%
“…In 2011, Behavioural Supports Ontario (BSO) was created as an effort to initiate system redesign, effecting changes at local, regional, and provincial levels to improve care for a broader population of older adults with cognitive impairments due to mental health problems, addictions, dementia or other neurological conditions who exhibit or are at risk of exhibiting responsive behaviours such as aggression, wandering, physical resistance, and agitation and their caregivers (Gutmanis, Snyder, Harvey, Hillier, & LeClair, ; Gutmanis et al., ). It has been demonstrated that effective implementation of interventions aimed at system change requires consideration of multiple factors at micro, meso, and macro levels with examination of the interplay between individual, organisational, community, and system factors (Chaudoir, Dugan, & Barr, ; Durlak & DuPre, ; Greenhalgh, Robert, MacFarlane, Bate, & Kyriakidou, ; Wandersman et al., ).…”
Section: Introductionmentioning
confidence: 99%